The Epidermal Growth Factor Receptor Ligand Amphiregulin Protects From Cholestatic Liver Injury and Regulates Bile Acids Synthesis. Issue 4 (4th March 2019) - Santamaría, Eva; Rodríguez‐Ortigosa, Carlos M.; Uriarte, Iker; Latasa, Maria U.; Urtasun, Raquel; Alvarez‐Sola, Gloria; Bárcena‐Varela, Marina; Colyn, Leticia; Arcelus, Sara; Jiménez, Maddalen; Deutschmann, Kathleen; Peleteiro‐Vigil, Ana; et al.
Abstract : Intrahepatic accumulation of bile acids (BAs) causes hepatocellular injury. Upon liver damage, a potent protective response is mounted to restore the organ's function. Epidermal growth factor receptor (EGFR) signaling is essential for regeneration after most types of liver damage, including cholestatic injury. However, EGFR can be activated by a family of growth factors induced during liver injury and regeneration. We evaluated the role of the EGFR ligand, amphiregulin (AREG), during cholestatic liver injury and regulation of AREG expression by BAs. First, we demonstrated increased AREG levels in livers from patients with primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC). In two murine models of cholestatic liver injury, bile duct ligation (BDL) and alpha‐naphthyl‐isothiocyanate (ANIT) gavage, hepatic AREG expression was markedly up‐regulated. Importantly, Areg –/– mice showed aggravated liver injury after BDL and ANIT administration compared to Areg +/+ mice. Recombinant AREG protected from ANIT and BDL‐induced liver injury and reduced BA‐triggered apoptosis in liver cells. Oral BA administration induced ileal and hepatic Areg expression, and, interestingly, cholestyramine feeding reduced postprandial Areg up‐regulation in both tissues. Most interestingly, Areg –/– mice displayed high hepatic cholesterol 7 α‐hydroxylase (CYP7A1) expression, reduced serum cholesterol, and high BA levels. Postprandial repression of Cyp7a1 was impaired in Areg –/– mice, and recombinant AREG down‐regulated Cyp7a1 mRNA in hepatocytes. On the other hand, BAs promoted AREG gene expression and protein shedding in hepatocytes. This effect was mediated through the farnesoid X receptor (FXR), as demonstrated in Fxr –/– mice, and involved EGFR transactivation. Finally, we show that hepatic EGFR expression is indirectly induced by BA‐FXR through activation of suppressor of cytokine signaling‐3 (SOC3). Conclusion: AREG‐EGFR signaling protects from cholestatic injury and participates in the physiological regulation of BA synthesis.